(untitled) (Bangladesh Journal of Agricultural Research, 2009)
Field experiments were conducted at the Regional Agricultural Research Station of Bangladesh Agricultural Research Institute, Jessore during rabi (winter) seasons of 1999-2001 to study the tillage and mulching effects on conservation of residual soil moisture, yield attributes and yield of mustard (cv. Daulat.). Three different tillage methods, namely minimum, reduced and conventional tillage were used in the main plots and three different mulch materials, namely rice straw, water hyacinth, black polythene including no mulch were used in the sup-plots. It was observed that reduced tillage and polythene mulch or rice straw mulch conserve more moisture than other tillage methods and mulch application. Tillage practice significantly influenced the dry matter, yield and yield components of mustard. Reduced tillage gave consistently the highest seed yield (969 kg/ha), while minimum tillage gave the lowest seed yield (92 kg/ha). Mulching also resulted in better crop growth and increased yield. Significantly higher seed yield (1164 kg/ha) was recorded from black polythene mulch followed by rice straw mulch (1089 kg/ha). The yield of mustard was obtained due to the interaction effects on reduced tillage and polythene mulch followed by conventional tillage and polythene mulch, which was found superior to all other treatments. Results revealed that polythene mulch or rice straw mulch accompanied by reduced tillage was economically profitable for mustard cultivation/production under rainfed condition. Key Words: Rainfed mustard, tillage, mulching. doi: 10.3329/bjar.v33i4.2303 Bangladesh J. Agril. Res. 33(4) : 597-606, December 2008